Leadership Networks: A Strategic Approach for the Department Chair's Development - Leda Stawnychko (Academic Chairpersons Conference Proceedings, 2023)
The interactive workshop will begin with a 20 min introductory presentation drawing on the results of an empirical study conducted at a comprehensive research university in Canada. The participants will be invited to analyze the importance of networks in the context of their own leadership development and to explore strategies to develop and nurture them.
Keywords: leadership networks; leadership development; department chairs; sustainable leadership; qualitative methods